Visualizing early allograft rejection: an M1 macrophage-specific GLUT1 probe predicts TCMR onset in renal transplantation - Wang, Zhaoxiang; Wei, Fanchao; Huang, Dayuan; Qi, Ruochen; Han, Shichao; Shi, Changhong; Song, Hongtao; Du, Yuxuan; Li, Zhengxuan; Li, Lang; Zhang, Jingliang; Ma, Shuaijun; et al. (Frontiers in Immunology, 2025)
BackgroundT cell-mediated rejection (TCMR) represents a leading cause of graft dysfunction and even patient mortality following transplantation. Percutaneous biopsy for monitoring T-cell-mediated rejection (TCMR) presents several inherent limitations, including its invasive nature, the risk of procedure-related infections, potential iatrogenic injury to the graft kidney, and issues related to delayed monitoring. This study seeks to identify novel monitoring modalities to achieve early, non-invasive, dynamic monitoring of allograft rejection.MethodsThe transplanted kidneys of Wistar-SD allogeneic kidney transplantation rats were analyzed by pathological methods and single-cell sequencing technology to identify the upregulated targets when rejection occurs. Based on these targets, a library was constructed and screened to obtain fluorescent probes for specific monitoring of rejection. After completing the safety verification of the probes, flow cytometry and in vivo imaging technology were used to verify the monitoring effect of the probes on rejection in vitro and in vivo, respectively.ResultsIn this study, we rationally developed a near-infrared fluorescent probe, XJYZ, for the in vivo imaging of M1 macrophages. We evaluated the capability of XJYZ for the early monitoring of rejection in an allogeneic renal transplantation model. In vivo imaging demonstrated that XJYZ preferentially accumulated within the allograft, enabling the early detection of dynamic changes in M1 macrophage infiltration.ConclusionsM1-type macrophages are recruited in large numbers in the early stage of transplantation and play a key role in the progression of rejection. Glucose transporter-1 (GLUT1) is crucial for M1-type macrophages to exert pro-inflammatory effects. In the early stage of rejection, due to the high metabolic demand of M1-type macrophages, the expression of GLUT1 is significantly upregulated. These findings highlight the potential of GLUT1 as a predictive biomarker for guiding early and precise monitoring of rejection. In conclusion, this study provides an alternative method for early and non-invasive monitoring of allograft rejection.